2007
DOI: 10.1073/pnas.0705069104
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary structures of tumor suppressor p53 and a specific p53–DNA complex

Abstract: The homotetrameric tumor suppressor p53 consists of folded core and tetramerization domains, linked and flanked by intrinsically disordered segments that impede structure analysis by x-ray crystallography and NMR. Here, we solved the quaternary structure of human p53 in solution by a combination of small-angle x-ray scattering, which defined its shape, and NMR, which identified the core domain interfaces and showed that the folded domains had the same structure in the intact protein as in fragments. We combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
193
2
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(223 citation statements)
references
References 51 publications
26
193
2
2
Order By: Relevance
“…These experiments would not have been possible using wildtype p53 but required the superstable quadruple mutant that has been key to our structural studies (22,24,25,(30)(31)(32): a half-life of 40 min at 37°C for formation of tetramers is longer than the half-life of 9-16 min for the spontaneous denaturation of wild-type p53 at 37°C (28). The combination of the high instability of wild-type p53 and its slow oligomerization has profound implications: unless there are special factors within the cell, p53 will spontaneously denature faster than it will form active tetramers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These experiments would not have been possible using wildtype p53 but required the superstable quadruple mutant that has been key to our structural studies (22,24,25,(30)(31)(32): a half-life of 40 min at 37°C for formation of tetramers is longer than the half-life of 9-16 min for the spontaneous denaturation of wild-type p53 at 37°C (28). The combination of the high instability of wild-type p53 and its slow oligomerization has profound implications: unless there are special factors within the cell, p53 will spontaneously denature faster than it will form active tetramers.…”
Section: Discussionmentioning
confidence: 99%
“…Isopropyl 1-thio-␤-D-galactopyranoside (IPTG) was added to a final concentration of 1 mM to induce expression. The cells were incubated for 15 h at 25°C before they were harvested and the proteins were purified as described (24,30) except expression of 13 C-and 15 N-labeled p53 was in M9 minimal medium supplemented with a vitamin mix together with 1 g/L 15 NH4Cl and 13 C D-glucose (30). Protein concentration was determined spectrophotometrically using a molar extinction coefficient 280 ϭ 20,400 M Ϫ1 cm Ϫ1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Active p53 is a tetrameric protein consisting of an oligomerization domain (OD), a DNA-binding domain (DBD), and a transactivation domain (TAD). Schematic representation (left) and crystal structures (right; PDB IDs: OD, 2J0Z; DBD, 2XWR; and TAD, 2L14) of p53 monomers (green, red, blue, and gold) in the predicted active conformation based on electron microscopy and small-angle X-ray-scattering reconstructions (Tidow et al 2007;Melero et al 2011). block the p300/CBP-mediated acetylation of p53 (Sabbatini and McCormick 2002), a modification that is critical for the tumor-suppressor functions of p53 (Brooks and Gu 2011).…”
Section: The Role Of Ordered and Intrinsically Disordered Domains In mentioning
confidence: 99%
“…The corresponding populations for the diameter measurements, corrected for tip effects, gave population 1 and 2, as shown in Table 2. We compared the dimensions obtained from our measurements with those in the literature (see Figure 1a.), 25,26,27 and found that most likely population 1 corresponds to dimeric flp53 protein, whilst population 2 corresponds to tetrameric flp53 protein.…”
Section: Introductionmentioning
confidence: 99%